Оптимизация процесса поиска неизвестного количества движущихся объектов - Grishin, I. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
A method of search process optimization of unknown amount of train objects is offered. A method is used for the radiolocation system in the conditions of stochastic vagueness and allows shortening substantially mean time of objects search.